National Archives, The Bill Of Rights - Evolution Of Personal Liberties Kit - Woestman, Kelly (Teaching History: A Journal of Methods, 1993)
The Bill of Rights: Evolution of Personal Liberties kit is an excellent example of scholars and teachers combining their expertise to produce a superior product for classroom instruction. As the tenth unit in this series of primary source material assembled by the National Archives, this set contains a selection of ten exercises that a teacher can use when discussing the Bill of Rights. This collection of 46 documents allows students to take a hands-on approach to their study of history.